Preparation of Ca modified Li2TiO3 ceramics pebbles and its activation energy calculation. (2017) - Kumar, Mohit; Sinha, Rohit Kumar; Yadav, Shlok; Sinha, S.K.; Raole, P.M.
Ca modified lithium titanate (Li2 TiO3 ) ceramics pebbles were prepared by method of sol-gel followed by urea-aceton spherodisation technique. Lithium titanate having monoclinic structure in pure phase was obtained. DTA/TG analysis of green sample was carried out to know the thermal reactions. Calcinations temperature was determined as 600°C. ICP test of sample was carried out to determine the purity of sample. Laser flash method was used to study thermal conductivity and diffusivity of the ceramics. The thermal conductivity of the sample at room temperature was about 3 W/m/K, which fell down to ~2.5 W/m/K at 600°C, after which it rises gradually to 4.0 W/m/K at 1000°C. Activation energy was calculated using Arrhenius equation and was obtained as 1.03 8eV/mole.